Q methodology and rural research - Previte, J.; Pini, B.; Mckenzie, Fiona Haslam (Sociologia Ruralis, 2007)
Traditionally, rural scholarship has been limited in its methodological approach. This has begun to change in recent years as rural researchers have embraced a range of different methodological tools. The aim of this article is to contribute to greater methodological pluralism in rural sociology by introducing readers to a method of research that is rarely engaged in the field, that is, Q methodology. The article describes the defining features of the approach as well as providing examples of its application to argue that it is a method that offers particular opportunities and synergies for rural social science research.